Self-healing materials : from fundamental concepts to advanced space and electronics applications - Aïssa, Brahim; Haddad, Emile I.; Jamroz, Wes R. (The Institution of Engineering and Technology, 2019)
This book addresses the key concepts of self-healing processes, from their occurrences in nature through to recent advances in academic and industrial research. It includes a detailed description and explanation of a wide range of materials and applications such as polymeric, anticorrosion, smart paints, and carbon nanotubes.
Keywords: Self-healing materials.; Biomimetics.; Optical fiber detectors.; Polymers.; elektronické knihy; electronic books